Inhibition of return is supramodal: a demonstration between all possible pairings of vision, touch, and audition. - Spence, C; Lloyd, D; McGlone, F; Nicholls, M; Driver, J (2000)
Inhibition of return' (IOR) refers to the delayed detection often found for targets at the same location as a preceding event. We examined whether IOR reflects a truly supramodal phenomenon, in an experiment designed to avoid criticisms of previous crossmodal research. We presented a random sequence of visual, tactile, and auditory targets to either the left or right of central fixation, and tested for IOR between targets in all three modalities when presented successively to the same versus different side. Speeded detection for targets in all three modalities was indeed slower if the preceding target had been presented from the same position, regardless of the modality, of this preceding target. These results demonstrate for the first time that IOR is truly supramodal.